2012
DOI: 10.1111/j.1755-0238.2012.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar ultraviolet radiation and canopy manipulation on the biochemical composition of Sauvignon Blanc grapes

Abstract: Background and Aims:New Zealand is exposed to relatively high solar ultraviolet (UV) radiation; such high irradiances of UV radiation having the potential to change the biochemical composition of plants. The aim of this study was to investigate the effects of UV radiation and the role of canopy leaves on berry biochemical composition in Vitis vinifera var. Sauvignon Blanc. Sauvignon Blanc is the major grape variety grown in New Zealand. Methods and Results: Leaves were removed from around the fruiting zones of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(112 citation statements)
references
References 46 publications
4
108
0
Order By: Relevance
“…Similarly, the UV exposure increased wine colour density, anthocyanin, total pigments, total phenolics and tannins by respectively 79%, 106%, 66%, 85% and 202%. These results are likely to be due to the increased flavonol and flavonoids due to the activation of genes of the phytopropanoid pathway in grape berries simulated by UV radiation (Gregan et al, 2012). However, some researchers reported that ambient UV radiation had no effect on total anthocyanins in grape berries (Keller & Torres-Martinez, 2002;Spayd et al, 2002).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, the UV exposure increased wine colour density, anthocyanin, total pigments, total phenolics and tannins by respectively 79%, 106%, 66%, 85% and 202%. These results are likely to be due to the increased flavonol and flavonoids due to the activation of genes of the phytopropanoid pathway in grape berries simulated by UV radiation (Gregan et al, 2012). However, some researchers reported that ambient UV radiation had no effect on total anthocyanins in grape berries (Keller & Torres-Martinez, 2002;Spayd et al, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…In this study, polycarbonate and acrylic sheet were used to block or transmit UV radiation, respectively, using the method of Gregan et al (2012). These two covering materials could transmit most of photo-synthetically active radiation, while they had considerably different transmission rate in UV region.…”
Section: Field Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, temperature plays and important role on flavonoid development (Huglin and Schneider, 1998), anthocyanin concentrations (Coombe, 1987;Tarara et al, 2008), proanthocyanidin (Cohen et al, 2012Zamora, 2003 and on various aroma compounds (Duchêne and Schneider, 2005;Reynolds and Wardle, 1993). Other climatic variables such solar radiation or water distribution are also important for the optimum development of color and aroma during ripening (Sebastian et al, 2015;Gregan et al, 2012), and also affect berry sizes and overall yield (Ubalde et al, 2010). However, within a specific climate zone, soil is the most important environmental factor controlling within vineyard vine development and fruit or wine quality (Sotés and Gómez-Miguel, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The work of Allen and Lacey (1993) and Falcao et al (2007) showed that IBMP levels in wines are lower when the temperature is higher during the growing season. This phenomenon is amplified by exposure of the grapes to light and the removal of the basal leaves that contain IBMP during the nouaison-grape closure stages of the vine (Ryona et al, 2008;Gregan et al, 2012.). Conversely, the IBMP content is higher in grapes from vigorous vines with a high vegetation density (Allen and Lacey, 1993).…”
Section: Temperature/light Relationship and The Aromatic Component Ofmentioning
confidence: 99%